Strategi STP Agensi Digital Marketing Tahap Perintisan untuk UMKM Kecil–Menengah - Fahmi Khairi Al Azmi; Hani Humaeriyah (INDO PUBLISHING, 2026)
This study aims to formulate a Segmenting, Targeting, and Positioning (STP) strategy for an early-stage digital marketing agency by focusing on micro, small, and medium enterprises (MSMEs) in the food and beverage and fashion sectors. The research is grounded in the observation that, although the demand for digital promotion continues to increase, the adoption of professional digital marketing services among MSMEs remains relatively limited. A descriptive qualitative approach with a case study design was employed. Data were collected through an exploratory survey involving 30 purposively selected MSME owners and were analyzed using descriptive and thematic techniques to identify dominant market patterns. The findings indicate that the food and beverage and fashion sectors demonstrate high visual promotional needs; however, most respondents have never utilized digital marketing services, thereby revealing a significant strategic opportunity for early-stage agencies. Based on these findings, the targeting strategy is directed specifically toward early-stage MSMEs within these sectors, while the positioning strategy emphasizes simple, affordable, educational, and transparent services tailored to the needs and constraints of beginner entrepreneurs. This study contributes to the development of empirically grounded service marketing strategies for start-up ventures and provides practical implications for digital marketing agency managers in determining segmentation focus and service differentiation. Future research is recommended to expand the number of respondents and the geographical scope in order to enhance the generalizability of the findings.